Percutaneous coronary intervention with transcatheter aortic valve replacement makes no difference! None? Really?. Issue 5 (20th January 2020) - Block, Peter C.; Kumar, Arnav
Key Points: Unless a patient who needs transcatheter aortic valve replacement (TAVR) presents with an acute coronary syndrome, "routine" percutaneous coronary intervention of coronary stenoses does not improve outcomes, even out to 5 years. Randomized clinical trials are needed to sort out the best strategies to treat the complex interaction of coronary disease and aortic stenosis, though they are unlikely to be performed. Without such evidence, patients undergoing TAVR need the judgment of a Heart Team to help strategize whether revascularization for CAD should be performed.